PENGARUH KONSENTRASI SODIUM TRIMETAPHOSPATE DAN SODIUM TRIPOLYPHOSPAT TERHADAP KARAKTERISTIK KIMIA PATI AREN MODIFIKASI - Abdul Rahim; Jugni Hadiustri Agape; Muhammad Fawzul Alif Nugroho; Syahraeni Kadir; Jusman Jusman; Usman Made; If'all If'all (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The utilizing of arenga starch is still limited in its use in the food or non-food industry, because it needs to be dual modified. The dual modification that has been done is acetylation and phosphorylation in various ratios of sodium trimethaphosphate (STMP) and sodium tripolyphosphate (STPP). The objectives of the study was to obtain an concentrations of STMP/STPP (99: 1, b / b) ratio which based on chemical characteristics at phosphate acetylated arenga starches (PAAS). The treatment used in this study consisted of dual modification of acetylation and phosphorylation using at different concentration of STMP / STPP ratio of 2%, 4%, 6%, 8%, 10%, and 12%. Observation parameters were acetyl percent, substitution degree (DS), phosphate content, moisture content, starch content, amylose content and ash content. The results showed that the best concentration of STMP / STPP ratio was 6% because it was produced PAAS with the highest percent acetyl and DS 10.52% and 0.48 respectively. PAAS water content is lower than native arenga starch. Pospor, starch and amylose content have been relatively constant after dual modification. PAAS ash content increases with increasing concentration of STMP / STPP ratio. The dual modification process would improve the chemical properties of the resulting modified starch.